﻿Film as a medium of communication for da'wah: analysis of religious elements in selected malay films - Rosmawati Mohamad Rasit; Mohd Salleh Hassan; Mohd Nizam Osman; Muhamad Sham Shahkat Ali (Penerbit Universiti Kebangsaan Malaysia, 2011)

(untitled)
﻿The use of film for conveying the message of da'wah is seen as a new approach that has to be taken as an opportunity This research uses a qualitative content analysis in dealing with religious elements in Malay feature films within the genre of (religious) drama. FINAS (2010) recorded that 26 films had been produced throughout the year 2009. Out of the 26 films, two were selected for the research by purposive sampling -categorized as films with religious elements -namely Syurga Cinta (2009) and Muallaf(2009) -Paradise of Love (2009) and Muslim Convert (2009). The research uses two important principles in film analysis, which are the story and plot, and the characters and character traits. The main objective of the research is to identify religious elements adopted in Malay films belonging to the religious genre in line with the concept of Islamic da 'wah or the opposite.